The Fading of Identity Politics and the Rise of Oligarchy in Selayar, South Sulawesi - Bakar, Abu; Kambo, Gustiana A; Bahtiar, M. Teguh Setyadi (UI Scholars Hub, 2025)
The fading of identity issues indicates that the direction of local politics in Selayar has shifted and changed. However, this change does not mean that it does not bring new problems to the local political landscape in Selayar, South Sulawesi, Indonesia. We aim to uncover the emergence of oligarchy in place of identity politics as a new phenomenon in the Selayar context. This research uses the concept of oligarchy to understand it, which is described qualitatively. In general, we argue that the failure of identity politics to consolidate power has given birth to oligarchies that are intertwined with familism in the local sphere. The emergence of oligarchy at the local level is strongly influenced by the disorientation of identity politics and the fragile socio-economic conditions of the community so that the practice of buying and selling votes cannot be avoided, which is used by oligarchs to take advantage unilaterally.